The Production and Reproduction Performance of North Kordofan Sub-type Sudan Desert Sheep under Irrigated Agriculture Land use, Gezira, Sudan - Sulieman, A.H.; Bashar, A.E.; El-Tahir, H.A.; A.H.Sulieman, Salma; EL Naeem, W.M.; EL Amin, A.I. (Journal of Veterinary Medicine and Animal Production, 2021)
A flock of North Kordofan (NK) Sub-type Sudan Desert Sheep was studied in the previously Animal Production Station at El Huda. Overall average of: 3.6±0.04, 17.2±0.44, 21.7±0.59, and 31.55±1.36 Kg, were obtained, respectively, for live weight at: birth, weaning (16 weeks), six and twelve months of age. Males had heavier weights at birth, 12 months and daily gain to 12 month compared to females. Daily gain to weaning was 122±5.0 vs 119±4.0 gm but non-significantly different for sex effect. Service/conception ratio, gestation length, lambing rate, were 1.00 vs 1.63, 153.1±0.71 vs 151.3±0.45 days, and 48.6 vs 67%, respectively, in the ewe lambs and mature ewes. Litter size differed in the two ewe groups, being bigger in the mature ewes due to the occurrence of multiple births and the increased number of ewes having lambs. The mature ewes had a lambing interval of 339.8±32.08 days. At breeding the young ewes were 313.76±12.56 days old and 48.1±2.82 Kg liveweight and they had their first offsprings when they were 473.12±15.08 days old.